2008
DOI: 10.1099/vir.0.83294-0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of type I interferons and interferon-inducible Mx genes during respiratory syncytial virus infection and reinfection in cotton rats

Abstract: Respiratory syncytial virus (RSV) is the primary cause of bronchiolitis in young children. In general, RSV is considered to be a poor inducer of type I (alpha/beta) interferons (IFNs). Measurement of active type I IFN production during infection in vivo is demanding, as multiple IFN subtypes with overlapping activities are produced. In contrast, Mx gene expression, which is tightly regulated by type I IFN expression, is easily determined. This study therefore measured Mx expression as a reliable surrogate mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
4
32
0
Order By: Relevance
“…It has been shown in both laboratory animals Significance was calculated using a two-way ANOVA. *, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. and humans, that systemic antibodies do not completely prevent early viral replication steps and innate immune responses (34,35,40). This may be explained by inadequate serum titers and/or insufficient access of antibodies to the airway lumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in both laboratory animals Significance was calculated using a two-way ANOVA. *, P Ͻ 0.05; **, P Ͻ 0.01; ***, P Ͻ 0.001. and humans, that systemic antibodies do not completely prevent early viral replication steps and innate immune responses (34,35,40). This may be explained by inadequate serum titers and/or insufficient access of antibodies to the airway lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Abortive replication in vivo can be monitored by comparing lung viral loads using the PFU assay and by the PCR detection technique and has been observed in animals treated prophylactically by virus neutralizing antibodies instilled systemically. Abortive replication still induces inflammatory immune responses via cytoplasmic recognition of genomic viral RNA and replication intermediates (35). Also, viral antigen expression might still occur.…”
Section: Expression Of Fcrn In Wt Bm-dcs and D1 Cells And Its Absencementioning
confidence: 99%
“…RSV can induce high levels of type I IFNs immediately upon infection, but this burst was shortlived with a sharp decline in type I IFNs production as the infection progressed, while influenza virus can induce durative high levels of type I IFNs [35]. Pletneva et al [37] also reported that type I IFNs were activated by RSV infection in the lung relatively early and transitorily during infection. Previous study has suggested that RSV activated interferon regulatory factor 3 (IRF-3), which is a key inducers of IFN-b, efficiently early in infection but that continued activation was observed only in cells infected by the NS1/NS2 gene deletion mutants [38].…”
Section: Cytokines Synthesis In Rsv Infectionmentioning
confidence: 95%
“…1 of each virus and analysing the accumulation of Mx1 mRNA by qRT-PCR. Mx1 is an IFN-stimulated gene that is commonly used to measure IFN signalling in response to infections (Hoenen et al, 2014;Holzinger et al, 2007;Pletneva et al, 2008). Mx1 expression values were normalized to the levels of viral RNA in order to account for variations in viral replication efficiency between the viruses.…”
Section: Induction and Suppression Of Ifn Response By Parental And Chmentioning
confidence: 99%